Cytokine Production and Human Cytomegalovirus Load in Allogeneic Hematopoietic Stem Cell Transplantation Outcome - TA Silva; JF Correia-Silva; RG Resende; MHNG Abreu; AL Teixeira; H Bittencourt; RS Gomez (International Journal of Immunotherapy and Cancer Research - Peertechz Publications, 2016)
Objective: To investigate the impact of cytokine levels (IL-1β, IL-6, IL-10, IFN-γ and TNF-α) and Human cytomegalovirus (HCMV) load in the saliva and blood on the survival of  llogeneic hematopoietic stem cell transplantation (allo-HSCT) recipients. Study Design: Samples were obtained from 63 patients 7 days before and 21 days after allo-HSCT. Cytokine levels were assessed by ELISA, and HCMV load was determined by real- me PCR. Results: The increase of IL-6 in the saliva and the reduction of IFN-γ in the blood before allo-HSCT were associated with increased risk of death. Moreover, the increase of IL-6 in the blood and of HCMV in the saliva after allo-HSCT were also associated with increased risk of death. Conclusions: Cytokine levels and HCMV load were associated with the increased risk of death. The findings suggest a potential function of these biomarkers in the determination of allo-HSCT survival.